Analysis of Transportation Development for Small Islands in Sumenep District, East Java Province - Mohammad Hidayaturrahman (Bappenas Working Papers, 2018)
This study aims to describe the economic potential of islands in Sumenep District. This study uses a qualitative descriptive approach, carried out by collecting data through observation, in-depth interviews, and data tracking. Sumenep District has the largest number of islands in East Java, 287 islands, spread across nine subdistricts. These islands have considerable economic potential, from oil and gas to fisheries, epinephelinae, cromileptes altivelis, and lobster. This area has a great need for the existence of a transportation network as a means of economic mobility of the community, which also affects the price of basic necessities far higher than the area of Sumenep Regency on the mainland, Madura Island and Java Island.